PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ong Aurellia Putri Sanjaya; Nur Cahyonowati (Diponegoro Journal of Accounting, 2022)
This study aims to examine and empirically prove the mediating role of profitability in the relationship between managerial ownership and stock returns. Managerial ownership will encourage managers to improve shareholders’ wealth, which can be done by increasing stock returns. Profitability is used as a financial ratio that measures the success of management as well as an information for shareholders about the condition of the company. This study uses secondary data obtained from observation and documentation. The population of this study are 158 manufacturing companies listed on the Indonesian Stock Exchange in 2017-2020. Based on the purposive sampling method, 33 companies met the sampling criteria. The research hypotheses were tested using coefficient of determination and t-test, while the mediation hypothesis used path analysis and sobel test. The results of this study indicate that managerial ownership has a positive effect on stock returns, managerial ownership has a positive effect on profitability, profitability has no effect on stock returns, and profitability fails in mediating the relationship between managerial ownership and stock returns.